PERCEPTION OF INFORMATICS STUDENTS ABOUT MATERIALS IN DISKRIT MATHEMATICS USING DOMAIN AND CODOMAIN FUNCTIONS - Dimas Midyan Alam; Alwi Rahmaan (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This study aims to determine the interest of Informatics students about the material in discrete mathematics that is most in demand. The population of this study was 20 students from the Informatics Department at Amikom University Yogyakarta. Data collection techniques using the interview method. The interview method is used to determine student interest in discrete mathematics course material that is in accordance with the actual conditions. In the discussion the author uses functions in discrete mathematics, namely with domain functions, codomain, and range. The results of this study indicate that the interests of Informatics students about matter have discrete mathematics in sufficient categories